GLUT4 as A Protein Target for T2DM Therapy with Natural Compounds - Sutandar, Vivi Hendra; Saleh, Mgs. Irsan; Maritska, Ziske (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
WHO reported 1.9 million death cases of diabetes patients in 2019. Diabetes is caused by damage in the pancreas which resulted in a lack of insulin or insulin resistance. Medication for T2DM mainly focuses on lowering blood glucose and treating affected organs. Current medications are still lacking, thus research is needed in finding novel medications to accommodate T2DM. This paper aims to present the current research on potential plant extract in increasing GLUT4 translocation in diabetes conditions. insulin resistance state affecting GLUT4 translocation which is important in affecting glucose uptake. Some research shows that plant extract proved to be potential in increasing the translocation of GLUT4 and helping lowering blood glucose levels.